IMPLEMENTASI DECISION SUPPORT SYSTEM METODE SIMPLE MULTI ATTRIBUTE RATING TECHNIQUE DALAM PEMILIHAN RUMAH KOST DISEKITAR KAMPUS UNIVERSITAS NEGERI MEDAN - Ronaldo Mardianson Sinaga; Fahri Aulia Alfarisi Harahap; Anggi Tasari; Deby Yandra Niska (Program Studi Teknik Informatika, Fakultas Teknik, Universitas Mataram, 2022)
The need for information on the boarding house and its location at this time is very important. However, due to the large amount of information about boarding houses and their available locations, the general public, especially students studying at universities, are confused about finding the location of a boarding house that suits their needs. Nowadays, many people use websites to find information about boarding houses, but the website only provides or provides information. Therefore, this research was built with the title